Financial Hardship: A Qualitative Study Exploring Perspectives of Seriously Ill Patients and Their Family - Dotolo, Danae G.; Pytel, Christina Clare; Nielsen, Elizabeth L.; Im, Jennifer; Engelberg, Ruth A.; Khandelwal, Nita (Journal of pain and symptom management, 2024)
Seriously ill patients, such as those who experience critical illness, and their families experience a variety of poor outcomes, including financial hardship. However, little is known about the ways in which these seriously ill patients and their families experience financial hardship. To examine seriously ill patients’ and families’ experiences of financial hardship and perspectives on addressing these concerns during and after critical illness. We conducted a thematic analysis of semi-structured interviews with seriously ill patients who recently experienced a critical care hospitalization (n=15) and family caregivers of these patients (n=18). Our analysis revealed three themes: 1) Prioritizing Survival and Recovery; 2) Living with Uncertainty—including experiences of prolonged uncertainty, navigating bureaucratic barriers, and long-term worries; and 3) Preferences for Financial Guidance. Our results suggest patients and families prioritize survival over financial hardship initially, and feelings of uncertainty about finances persist. However, patients and family caregivers are reluctant to have their physicians address financial hardship. Our findings suggest that the acute and time sensitive nature of treatment decisions in critical care settings provides a unique context for experiences of financial hardship. Additional research is needed to better understand these experiences and design context-sensitive interventions to mitigate financial hardship and associated poor patient- and family-centered outcomes.